Implementasi Metode Preference Selection Index Dalam Penentuan Jaringan Dan Pemanfaatan Internet Pada Provinsi Indonesia - Dewantara, Rizki; Cakranegara, Pandu Adi; Wahidin, Ahmad Jurnaidi; Muditomo, Arianto; Sudipa, I Gede Iwan (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The era of digital society is strongly supported by the development of information and communication technology, along with the use of the internet by the community, making the digital era help every community activity. The progress of internet development in Indonesia cannot be separated from the distribution of network infrastructure in all urban (urban) and rural (rural) areas in all provinces in Indonesia. Based on data from the Central Statistics Agency (BPS) for the period 2017 - 2020, this study aims to determine which of the 34 provinces in Indonesia are provinces that have a strong and stable internet network in urban and rural areas, as well as regions in Indonesia whose people are significantly utilizing the use of the internet in their daily activities in both urban and rural areas. The selection process uses eight assessment criteria from aspects of the expansion and distribution of internet network quality and internet utilization for rural and urban communities in the province of Indonesia. In this study, the method of solving the problem of multi-criteria decision-making is the Preference Selection Index (PSI) method. The results of the final calculation of the PSI method from 34 alternatives determine the five best provinces for expanding the internet network and internet utilization in 2020, namely the alternative provinces of Central Java, West Java, East Java, South Sumatra, and Aceh.